Mechanism of Improvement of Customs Innovations, Based on Indistinct and Multiple Approach at an Assessment of Risk Level of Violation of Customs Rules - Irina Aleksandrovna Topkova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The variety of the existing methods of an assessment of risk level of violation of customs rules for the purposes of customs control, and need of the accounting of a set of the factors determining the level of this risk define need of formation of qualitatively new methodical approaches. Possibility of application for the solution of similar problems of systems of fuzzy logic, in particular, of a package of the applied Fuzzy Logic programs of the MATLAB computing system is shown in the article. The technique, realized on the example of the goods classified in a commodity subsubposition 7323999900 FEACN of Customs Union - “Kitchen products from carbonaceous steel”.